Acute acalculous cholecystitis on a COVID-19 patient: a case report. (October 2020) - Mattone, E.; Sofia, M.; Schembari, E.; Palumbo, V.; Bonaccorso, R.; Randazzo, V.; La Greca, G.; Iacobello, C.; Russello, D.; Latteri, S.
Abstract: Introduction: We report an extremely rare case of acute acalculous cholecystitis on a COVID-19 patient. In our knowledge, this is the first report of laparoscopic cholecystectomy performed on a COVID-19 patient. Presentation of case: A COVID-19 patient was diagnosed with acute acalculous cholecystitis and a multidisciplinary team decided to perform a percutaneous transhepatic biliary drainage (PTBD) as the first treatment. SARS-CoV-2 RNA was not found in the bile fluid. Because of deterioration of the patient's clinical conditions, laparoscopic cholecystectomy had to be performed and since the gallbladder was gangrenous, the severe inflammation made surgery difficult to perform. Discussion: Acalculous cholecystitis was related with mechanical ventilation and prolonged total parenteral nutrition, in this case the gangrenous histopathology pattern and the gallbladder wall ischemia was probably caused by vascular insufficiency secondary to severe acute respiratory distress syndrome of COVID-19 pneumonia. The percutaneous transhepatic gallbladder drainage (PTBD) was performed according to Tokyo Guidelines because of high surgical risk. Laparoscopic cholecystectomy was next performed due to no clinical improvement. The absence of viral RNA in the bile highlights that SARS-CoV-2 is not eliminated with the bile while it probably infects small intestinal enterocytes which is responsible of gastrointestinal symptoms such as anorexia, nausea, vomiting, and diarrhoea. Conclusions: Although the lack of evidence and guidelines about the management of patient with acute cholecystitis during COVID-19 pandemic, laparoscopic cholecystectomy, at most preceded by PTGBD on high surgical risk patients, remains the gold standard for the treatment of acute cholecystitis on COVID-19 patients. Highlights: Coronavirus disease-19 (COVID-19) has spread to several countries around the world and has become an unprecedented pandemic. Cholecystitis was probably caused by vascular insufficiency secondary to respiratory distress syndrome of COVID-19 pneumonia. SARS-CoV-2 probably infects small intestinal enterocytes which is responsible of gastrointestinal symptoms such as diarrhoea. Laparoscopic cholecystectomy, remains the gold standard for the treatment of acute cholecystitis on COVID-19 patient.